Anomalous changes in ionospheric TEC during an earthquake event of 13–14 April 2010 in the Chinese sector - Aggarwal, Malini (My University, 2015)
The earth’s ionosphere is considered susceptible to the seismic effects and the detection of such ionospheric perturbations associated with the earthquake has become a challenge for the short-term prediction of earthquakes. In this paper, an investigation of the changes in the ionospheric behavior is reported which may be associated with M 6.9 and its aftershock of 6.1 magnitude earthquakes at Qinghai station (geog. 33.19N, 96.75E, geom. 23.90N, 169.98E) which occurred on 13 April (23:49 UT, 06:19 LT on 14 Apr) and 14 April 2010 (01:25 UT, 06:55 LT) respectively. The observations are made using ionospheric total electron content (TEC) obtained from 10 available IGS stations in the Chinese and 2 in the Indian sector to detect seismo-ionospheric anomalies if they exists. We found anomalous depletions in the ionospheric regions 3–4 days (on 10 April 2010) up to 4 TECU before the earthquake over stations close to the epicenter (<1700 km). The anomalous changes in the ionosphere are observed firstly over a distant station (wuhn, 0800–1600 UT) during afternoon to midnight hours and few hours later over the near-by stations to the epicentre in the nighttime (1500–2300 UT, 2100–0500 LT). Our results from the case study suggest that these anomalies in ionospheric TEC may be the possible seismo-ionospheric signatures for the considered earthquake in the Tibetian plateau region. 2015 COS
Keywords: Earthquake; Ionosphere; Total electron content (TEC)